Avaliação do progresso das nações: uma aplicação na América do Sul, Costa Rica e México - Campetti, Pedro Henrique de Morais (Universidade do Vale do Rio dos Sinos, 2014)
Worldwide, there is a search for new models to assess the societal progress. Economic growth has its value, but new priorities are needed if societies are to achieve higher levels of wellbeing. This paper aims to propose a multidimensional measure of progress to be used in South America, Costa Rica and Mexico. For this, it was analyzed 50 studies from different research centers that have similar objectives as this study and 14 were selected to be used as reference to construct a framework, that provides a conceptual approach and a logical structure with the domains and dimensions needed to evaluate progress. Through this framework, 50 indicators from 12 different databases were listed, which were used for a broad review of the progress and well-being, considering the period of analysis as the first decade of the XXI century, and that take into account economic, social, environmental, subjective, and other factors. The research methodology used was based on the z-scores method, to normalization of the data, and shift-share method, to analyze and rank the countries. The results indicate that Economy and Employment dimensions are those that contributed more to the countries' progress, while the Environment dimension caused the higher regress. Moreover, it was established a ranking of the progress, headed by Uruguay and followed by Chile, Costa Rica, Argentina, Brazil, Mexico, Venezuela, Colombia, Paraguay, Peru, Ecuador and, in the last position, Bolivia. Finally, Brazil was the country that has most progressed over the period, and Mexico has less progressed.
Keywords: Progresso; Progresso social; Bem-estar; Método estrutural-diferencial; Progress; Social progress; Well-being; Shift-share method; ACCNPQ::Ciências Sociais Aplicadas::Economia